(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2025)
This academic article investigates the multifaceted effects of globalization on language acquisition and educational practices. It provides a critical analysis of the historical dissemination of dominant world languages – primarily English and French – through colonization, and the subsequent marginalization of indigenous and minority languages.